Risk analysis and management for projects : a strategic framework for managing project risk and its financial implications (ICE Publishing, 2014)
Risk and uncertainty surround every human activity and influence everything we do. RAMP (Risk Analysis and Management for Projects) is a well-established framework for analysing and managing the risks involved in projects, whether large or small. With an emphasis on the strategic and financial aspects, this practical working guide will assist planners, engineers, accountants, actuaries, lawyers, project managers, public administrators and anyone else who is involved with a project's success.